2013
DOI: 10.4236/ojog.2013.31011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycated Albumin (GA) and Glycosylated Hemoglobin (A1C) in monitoring glycemic excursions during pregnancy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…7 Seshiah and colleagues found that the mean age was 27.10±4.05 years and 23.80±3.61 years in case and control group respectively, which is also comparable with the present study. 9 On the other hand, Sugawara and colleagues conducted a study which found the mean age was 35.1±4.6 years in patients with gestational diabetes mellitus and 34.9±3.5 years in control group, which is higher than the present study. 10 The higher mean age obtained by the above authors maybe due to striking variations in ethnicity, geographical variations, racial, and genetic causes may have significant influence on gestational diabetes mellitus in their study subjects.…”
Section: Discussioncontrasting
confidence: 78%
“…7 Seshiah and colleagues found that the mean age was 27.10±4.05 years and 23.80±3.61 years in case and control group respectively, which is also comparable with the present study. 9 On the other hand, Sugawara and colleagues conducted a study which found the mean age was 35.1±4.6 years in patients with gestational diabetes mellitus and 34.9±3.5 years in control group, which is higher than the present study. 10 The higher mean age obtained by the above authors maybe due to striking variations in ethnicity, geographical variations, racial, and genetic causes may have significant influence on gestational diabetes mellitus in their study subjects.…”
Section: Discussioncontrasting
confidence: 78%